Comparative Analysis of Lycorine in Wild Plant and Callus Culture Samples of Hymenocallis littoralis by HPLC-UV Method - Sreeramanan Subramaniam; Jeevandran Sundarasekar; Geethaa Sahgal; Vikneswaran Murugaiyah (The Scientific World Journal)
The Hymenocallis littoralis, an ornamental and medicinal plant, had been traditionally used for wound healing. In the present study, an analytical method using HPLC with ultraviolet detection was developed for the quantification of lycorine in the extracts of different parts of wild plant and tissue culture samples of H. littoralis. The separation was achieved using a reversed-phase column. The method was found to be accurate, repeatable, and sensitive for the quantification of minute amount of lycorine present in the samples. The highest lycorine content was found in the bulb extract (2.54±0.02 μg/mg) whereas the least was in the root extract (0.71±0.02 μg/mg) of the wild plants. Few callus culture samples had high content of lycorine, comparable to that of wild plants. The results showed that plant growth regulators, 2,4-dichlorophenoxyacetic acid (2,4-D) alone at 4.5 μM (2.58±0.38 μg/mg) or a combination of 2,4-D at 9.00 μM with 4.5 μM of 6-benzylaminopurine (BAP), were the optimum concentrations for the production of high lycorine (2.45±0.15 μg/mg) content in callus culture. The present analytical method could be of value for routine quantification of lycorine in the tissue culture production and standardization of the raw material or extracts of H. littoralis.